A construção de uma razão decolonial nos cursos de direito a partir do pensamento complexo e do pluralismo jurídico e a busca pela efetivação dos direitos humanos fundamentais - Costa, Lucas Kaiser (2019)
Western modernity was founded on the pillars of scientific knowledge and the modern state law, so that while the first sought to inform the criteria of truth and falsehood for explanations about life, the second established the form of organization of modern states and social regulation. Its other face, the coloniality, tried to demarcate the land of the possible, colonizing the power, the being and the knowledge in the zones objects of the colonization; through the violent processes of domination and assimilation, subjugated the experiences produced there. These reflexes spread to the centers of knowledge production - the universities - with legal education, influenced by the scientistic positivism and colonized as a modern pillar, followed by the same path, that is, producing an anachronistic and sectarian knowledge, decontextualized from social demands. The rationality forged from modernity / coloniality, totalizing its hegemony as the only possible reality, making invisible the colonial forms of knowledge that did not reproduce it. In this sense, the present study, based on the methodology of the "sociology of absences", Boaventura de Sousa Santos, seeks to verify how complex thinking and legal pluralism could contribute to the construction of a decolonial reason in law courses. For this, the work was divided into three chapters are concerned with: to analyze the paradigm of modernity, presenting its indolent rationality and the rise of social fascism, also observing the role played by the law and the necessity of a paradigmatic transition; discuss the theoretical categories of epistemological invisibility and unconventional knowledge in a context of colonialism and coloniality and its reflexes in legal education in Brazil; to examine the epistemological perspectives for the construction of a decolonial reason in the courses of law, in order to, finally, from the knowledge of fundamental human rights, demonstrates the demand for a complex paradigm, able to recognize and to materialize rights redefined from the pluralization of dogmatic law, making possible the construction of this decolonial reason, which, taking the right as freedom, would have the ability to mitigate the abyssality existing between the "street" and the "gown".